Virtual instrumentation: A practical approach to control and supervision process - Lemos, Marilza A. [UNESP]; Brunini, Danilo M. [UNESP]; Botura Jr., Galdenoro [UNESP]; Marques, Marcio A. [UNESP]; Rosa, Luiz Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This work describes a control and supervision application takes into account the virtual instrumentation advantages to control and supervision industrial manufacturing stations belonging to the modular production system MPS® by Festo. These stations integrate sensors, actuators, conveyor belt and other industrial elements. The focus in this approach was to replace the use of programmable logic controllers by a computer equipped with a software application based on Labview and, together, performs the functions of traditional instruments and PLCs. The manufacturing stations had their processes modeled and simulated in Petri nets. After the models were implemented in Labview environment. Tests and previous similar works in MPS® installed in Automation Laboratory, at UNESP Sorocaba campus, showed the materials and methods used in this work allow the successful use of virtual instrumentation. The results indicate the technology as an advantageous approach for the automation of industrial processes, with gains in flexibility and reduction in project cost. © 2011 IEEE.
Keywords: automation; Labview; manufacturing; supervision; virtual instrumentation; Conveyor belts; Industrial manufacturing; Industrial processs; LabViEW; Modular production system; Project cost; Software applications; Virtual Instrumentation; Automation; Belt conveyors; Computer programming languages; Computer science; Manufacture; Petri nets; Process control